Aspectos léxicos de la traducción del Canzoniere por Enrique Garcés (1591) - Garribba, Aviva (Cuadernos de Filología Italiana, 2005)
Enrique Garcés’ translation of Petrarch’s Canzoniere is a late product of the dissemination of Petrarquism in the Hispanic world. The author is a Portuguese by birth who spent almost all his life in Peru. The vo c a bu l a ry of his translation hardly reveals the translator’s origin while it is full of Italianisms. Some of these words had already been introduced in the Spanish lexicon through the poetic language, others were less known. In addition, his translation includes calques and rather daring borrowings from Italian. The article contains the analysis of the translation of some key-words of Petrarch’s Can -zoniere.